The rural community's perception in relation to the transformation of agricultural practice from traditional farming to commercial farming :a case study at Kpg. Sambir, Kota Samarahan, Sarawak - Liew, Chiew Ing (Faculty of Social Sciences, 2002)
This research is aimed to identify the overall perception of the rural community towards the transformation of agriculture from traditional farming to commercial farming. It focuses on the influences of the external factors that had been determined as the major driving forces (economic, government and social forces), which led to the transformation of agricultural practices in rural areas. In particular, this research was also intended to study the relationship among the driving forces and demographics factors in influencing the respondent's opinion or thingking regarding the issue on the trasformation of agriculture.